A Study on Stator Design for Electromagnetic Noise Reduction in Washing Machine Motor - Kim, Kwangsoo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Received:11 november 2020; Accepted: 27 December 2020; Published online: 05 April 2021 Abstract : For low cost, spoke type ferrite magnet motors with small air gap are using to washing machine. At that time, a noise problem occurs, so a design to reduce the noise is required. In the washing machine, set noise increased due to the reduction of air gap of motor at high speed spin mode. Not only the overall noise, but also the harmonics noises are greatly increased at set. As a result of set noise test and noise analysis through finite elements method, a stator tooth shoe shape in which the magnetic flux changes rapidly is cause of noise. Its shape creates many harmonics of load torque. The harmonics component of the load torque increases the overall noise of the set. The harmonics noise of the set has a large correlation with radial force component as well as the torque ripple. Especially, it is found that the harmonics noise of the set is related to harmonics component of load torque and the harmonics component of the radial force at stator tooth. The noise is reduced by applying the new design of stator tooth shoe that can minimize the change in magnetic flux through the noise cause analysis. Through this research, the harmonics noise as well as overall noise are reduced at small airgap motor. Therefore, it is possible to develop cost reduction motor for washing machine.